Evolução do número de acidentes do trabalho na região Sul do Brasil de 2008 a 2013 - Peripolli, Angélica (2016)
The accelerated process of technological innovation has provided changes in work organization, and it shows therefore an expansion on work overload, resulting in a high number of accidents. Considering the importance of the issue and the possibility of contribution about it, this study aimed to analyze the types of labour accidents, in Southern Brazil, from 2008 to 2013, according to sociodemographic and temporal characteristics, besides using the Box-Jenkins method to assess the evolution and forecast the number of accidents. Were considered the records made available by DATAPREV on Historical Database of the Statistical Yearbook of Social Security. The descriptive analysis was performed by gender and age group, besides the comparison of the number of accidents between the years considering the economic activities and elements of the ICD-10. To adjust the time series models and calculation of forecasts, it was used the Box-Jenkins methodology. The characterization of labour accidents allowed identify the following scenario: the state of Rio Grande do Sul presented in absolute terms, the largest quantities of industrial accidents, followed by Paraná. Typical accidents were the most frequent, indicating that the vast majority of workplace accidents occur in the workplace. Moreover, these accidents occur mostly among men and workers under 34 years old. Among the models found in this research, all of them showed seasonal component, except those regarding the number of labour accidents by disease in Santa Catarina and Paraná, which had only components of moving averages and autoregressive, respectively, as well as an integration component. It was concluded that, when using the time series methodology it is possible to obtain an important support of orientation and encouragement to the monitoring data related to labour accidents. It is noteworthy that, although the databases can present filling deficiencies, is important that let there be permanent disclosure of this informations in order to sensitize the institutions involved to achieve continuous qualification of this source of knowledge about the profile of labour accident.